1973
DOI: 10.1111/j.1528-1157.1973.tb03954.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Concentrations of Free Diphenylhydantoin and their Relationship To Clinical Intoxication

Abstract: SUMMARY A rapid and inexpensive method to determine the degree of protein binding of diphenylhydantoin (and other anticonvulsants) is described; it is applicable to screening large samples of patients. The method was used in 25 selected subjects to test the hypothesis that degree of intoxication with diphenylhydantoin is related more to the serum concentration of free than of total diphenylhydantoin. The results support the hypothesis. It is suggested that the method could be used more widely and that it would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0
2

Year Published

1975
1975
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(58 citation statements)
references
References 4 publications
2
54
0
2
Order By: Relevance
“…Early studies suggested that the inter-subject variability in degree of protein binding of phenytoin may be considerable and that the free phenytoin concentration might be better correlated with clinical toxicity (Booker & Darcey, 1973;Hooper et al, 1974;Bochner et al, 1974). The latest study of phenytoin binding (Peterson et al, 1983) has reopened the controversy as to the degree of interindividual variation in binding in otherwise healthy epileptic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies suggested that the inter-subject variability in degree of protein binding of phenytoin may be considerable and that the free phenytoin concentration might be better correlated with clinical toxicity (Booker & Darcey, 1973;Hooper et al, 1974;Bochner et al, 1974). The latest study of phenytoin binding (Peterson et al, 1983) has reopened the controversy as to the degree of interindividual variation in binding in otherwise healthy epileptic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Phenytoin is known to be highly bound to plasma proteins (approximately 90%). If there is large interpatient variability in the extent of phenytoin binding as some previous studies have suggested (Booker & Darcey, 1973;Bochner et al, 1974;Peterson et al, 1982), the total drug concentration might be a less reliable predictor of clinical effect than the free drug concentration. We thus decided to investigate the variability in phenytoin binding in epileptic patients receiving the drug.…”
Section: Introductionmentioning
confidence: 99%
“…As unbound drug represents the active form which equilibrates with tissues and because of the potential variability in phenytoin protein binding, it is desirable that the active unbound rather than the total concentration of the drug is measured in monitoring therapy. It has already been shown that phenytoin toxicity correlates better with the unbound rather than the total concentration of the drug (Booker & Darcey, 1973). The correlation between the unbound concentration and the therapeutic effect has not been formally examined although phenytoin saliva concentration, which reflects unbound plasma concentration, has been shown to relate well with clinical effect (Knott et al, 1982;McAuliffe etal., 1977;Reynolds etal., 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Modification of plasma protein binding due to diseases or displacing effects of other drugs has been shown to alter dramatically the toxic effects of several compounds (Reidenberg & Affrine, 1973;Anton, 1973). Recent data (Booker & Darcey, 1973;Glassman, Hurwic, Kanzler, Shostak & Perel, 1974) tend to suggest that, at variance with previous results (BorgA, Azarnoff, Forshell & Sjoqvist, 1969), important inter-individual differences in plasma protein binding may be observed in patients undergoing chronic treatment, in the absence of specific phenomena such as displacement, or alteration in proteinemia. Such conditions may be of importance for the therapeutic outcome and give an explanation of the considerably large therapeutic range observed for several drugs.…”
Section: Introductionmentioning
confidence: 99%